Towards a new definition of areal surface texture parameters on freeform surface: Re-entrant features and functional parameters. (July 2019) - Pagani, Luca; Townsend, Andrew; Zeng, Wenhan; Lou, Shan; Blunt, Liam; Jiang, Xiang Qian; Scott, Paul J.
Highlights: A method to compute the hybrid and functional roughness parameter is presented. Two surface reconstruction methods are investigated: Bezier surfaces and triangular meshes. The comparison with the texture parameters defined in the ISO 25178-2 is analysed. The method can be applied to meshes measured using computed tomography. The proposed method is suitable for additive manufacturing parts. Abstract: Characterisation of freeform surfaces is an increasingly importance area of metrology. Currently the characterisation of surfaces is performed using data that can be represented by a height map. Modern measurement devices allow the acquisition of surfaces with complex shapes that cannot properly be analysed using the current texture parameters definition. In this paper a method to characterise both freeform surfaces and surfaces with re-entrant features is proposed. Two surface approximation methods are investigated: triangular mesh and Bézier surface. The proposed method will be compared with a method able to extract the ISO 25178-2 areal texture parameters from a triangular mesh.